(untitled) (Northern International Medical College Journal, 2017)
Background : Hirschsprung disease (HD)is a common cause of intestinal obstruction. Definitive treatment is to excise aganglionic segment and anastomosis with anal remnant. Objective : The aim of the study was to analyze the short term outcome of children who have undergone the Classic swenson abdominoperineal pull through operation in the treatment of Hirschsprungs disease. Methods : This Prospective study had been carried out in the department of paediatric surgery, Dhaka shishu (Children) Hospital during the period of January 2013 to January 2016. Total 50 patients with Hirschsprungs disease with or without colostomy except total colonic aganglionosis were included in this study.We also excluded those patients with major co-morbidities and patients who did not agree to close stoma within 12 weeks of pull through. Consideration was given to postoperative complications(Cuff /anastomotic/pelvic abscess, wound infection, anastomotic leakage,fecal incontinence, urinary incontinence, mortatality), operation time and post operative hospital stay and as well as the short term outcome. Result : Among the study population 36 (72%) were male and 10(28 %) were female with a male female ratio of 2.5:1. Mean age at presentation was 17.96±12.05 months.Thirty eightpatients had diverting colostomy and underwent staged procedure.On the other hand 12 patients had no colostomy and underwent single stage procedure.Four patientsdeveloped anastomoticabcess, 3patients developed urinary incontinence,4 fecal incontinence and 2 patients developed post operative intestinal obstruction.The mean Operation time was114.14±13.02 minutes and mean hospital staywas 6.18±1.83 days.Thirty seven patients were discharged without any complications. Conclusion : The Classic Swensons procedure is an effective procedure in the treatment of HD . Northern International Medical College Journal Vol.8(1) July 2016: 185-188